Evaluation of queen cell acceptance and royal jelly production between hygienic and non-hygienic honey bee (Apis mellifera) colonies. - Khalid Ali Khan; Hamed A Ghramh (PLoS ONE, 2022)
Honey bees are crucial for pollination services globally and produce important hive products including honey, royal jelly, pollen, and propolis that are being used commercially in food, cosmetics, and alternative medicinal purposes. Among the bee products, royal jelly (RJ) has long attracted scientists' interest because of its importance in honey caste differentiation. The present research was carried out to determine the acceptance rate of queen cells, and RJ production between the hygienic and non-hygienic lines. Further, this study unveils the effect of pollen substitute diets on the queen cell acceptance rate and RJ yields between both bee stocks. Results showed that the uncapped brood cells and dead brood's removal percentage was significantly more in hygienic bee colonies in comparison to non-hygienic bee colonies (p < 0.05). The average percentage of larval acceptance was statistically higher in hygienic lines (64.33 ± 2.91%) compared to non-hygienic lines (29.67 ± 1.20%). Similarly, the RJ mean weight per colony differed statistically between both bee stocks (p<0.001), which were 12.23 ± 0.52 g and 6.72 ± 0.33 g, respectively. Moreover, our results demonstrated that a significant difference was observed in larval acceptance rate, RJ yields (per colony and per cup) between both bee stocks those fed on various diets. However, no significant difference was recorded in RJ yields (per colony and per cup) between both bee stock that feeds on either commercially available pollen or pollen substitute. This study may provide future applications in helping bee breeders to choose the bees that carry a higher level of hygienic behavior with high RJ production traits.